Evaluation of the Role of Crucial Impacts on Networks for Technological Innovation - Anderson, Henry Junior (Univerzita Pardubice, 2020)
Technological innovation, in recent times, has been pivoted as the foundation of regional competitive advantage. Its generation has grown to a multi- interactive structure involving multiple elements ranging from human capital, financial capital, social capital and structural capital and knowledge interactions. In effect, some regions have pivoted their funding acquisitions on the best innovating firms whilst others focus more on creation of tructures to assist Small and Medium Scale Enterprises (SMEs) to nurture their innovation base appreciably for a higher regional competitive advantage. In light of competition from other states, the European Union have initiated funding schemes like Horizon 2020, aside regional targets of for research and development expenditure, to strongly propel the innovation status of the bloc. Other framework conditions such as human, social and structural capital have been focused on as well, however, there have been arguments about their actual role played. Literature have portrayed them to have varying and contrasting effect in the eco-system for creation of technological innovation in various contexts ranging from regional need to partners involved and even to the location as well whilst there are also arguments against their actual role in supporting technological innovation. In that regard, this research intends assess the contributory role of financial, interactive, institutional and structural factors in the network of technological innovation generation in the European Union.
Keywords: technologické inovace; lidský kapitál; spolupráce; financování; inovátoři; technological innovation; human capital; cooperation; funding; innovators